Career intervention program to promote academic adjustment and success in higher education - Célia Sampaio; Célia Sampaio; Catarina Luzia de Carvalho; Maria do Céu Taveira; Maria do Céu Taveira; Ana Daniela Silva; Ana Daniela Silva (Frontiers in Education)
IntroductionThe transition to higher education can be challenging for many students, requiring developing skills and strategies to help them overcome various challenges. Adjustment to university is a multifaceted process involving several dimensions. Given the difficulty that a significant percentage of students face in this process, the lack of adaptation to higher education has been widely studied, as it is often associated with academic failure and dropping out of school. To mitigate these risks, career interventions have emerged as an essential support, helping students to develop personal resources such as resilience, time management, and decision-making capacity. The aim here is to present a career intervention program focused on promoting the adjustment and academic success of first-year undergraduate or integrated master’s students and evaluating the participants’ feedback on this intervention.MethodologyThis intervention program aimed to provide students with an opportunity to reflect on their adjustment process to the University, identifying possible areas of vulnerability, providing personalized feedback, and proposing modules of learning and personal and academic development that would favor the adjustment and academic success process. Additionally, it aimed to organize, systematize, and make known the support structures existing at the University to which students can resort in possible situations of psychosocial vulnerability and support for academic and career development. This intervention was based on and used a computer platform developed within the framework of the SUnStar project. The intervention took place over 6 weeks using the Teams platform and consisted of three modules, with module two divided into different sessions and topics. Seventy-four university students participated in the intervention, 56 (75.7%) of whom were female. A questionnaire with four Likert-type questions was designed to evaluate the sessions by the students.ResultsThe session “Pursuing my UMinho Career: Institutional Support Structures” consistently received the highest ratings across multiple evaluation criteria. In contrast, the “Social Networks and Cooperation” session received the lowest, although all sessions were rated above the average response point. The results are discussed regarding their relevance in an academic context and their implications for future interventions with this target group.